Analysis Of The Effectiveness Of Hemorrhagic Shock Management Protocols In The Field And The Effect Of The Type Of Intravenous Fluids Given On The Stability Of Vital Signs Of The Injured Within The Saudi Red Crescent Services (The Review of Diabetic Studies, 2025)
This research aims to analyze the effectiveness of hemorrhagic shock management protocols in the field, and to study the effect of the type of intravenous fluids given on the stability of vital signs of injured people within the Saudi Red Crescent services. The study was based on the descriptive analytical approach, and the data were collected through a field questionnaire directed at workers in emergency and ambulance teams. The results showed that the level of adherence to approved protocols is generally high, and that staff demonstrate a good understanding of the importance of applying initial resuscitation steps and controlling bleeding before administering fluids. The results also showed that the type of intravenous fluid used has a clear effect on the stability of the vital signs of the injured, especially in cases of severe bleeding. In contrast, the study revealed some field obstacles related to the availability of appropriate intravenous solutions and sometimes weak administrative support, which calls for strengthening training and supporting equipment to implement the protocols more effectively. The researcher recommends the need to update the training programs for paramedics, unify communication mechanisms with hospitals to receive critical cases as quickly as possible, in addition to improving the field supply of intravenous fluids appropriate for hemorrhagic cases.